Determination of birefringence of biological tissues using modified PS-OCT based on the quaternion approach - Ke, Qiuqing; Li, Ke; Wu, Weijie; Li, Wangbiao; Chen, Haiyu; Cai, Renhui; Li, Zhifang (Frontiers in Physics, 2023)
A modified Spectral domain polarization sensitive optical coherence tomography (SD-PS-OCT) system with circularly polarized light as reference combined with a quaternion approach is presented for determination of birefringence of biological tissue. In the modified SD PS-OCT, there is not any bulk polarization optical elements in both arms of reference and sample. Then, the Stokes vector of backscattered light was employed to characterize the birefringence of biological tissue based on quaternion approach, which directly establish the relationship between Stokes vectors of backscattered light and Jones matrix of sample. The birefringence of tissue including retardance and fast axis orientation will be calculated in the form of the analytic solution by theoretical analysis. The polarization properties of myocardial tissue in vivo are quantitatively reconstructed based on the proposed method. This study suggests that SD PS-OCT could be improved for potential clinical applications.